Flap Venous Congestion and Salvage Techniques: A Systematic Literature Review. Issue 1 (January 2021) - Boissiere, Florian; Gandolfi, Silvia; Riot, Samuel; Kerfant, Nathalie; Jenzeri, Abdesselem; Hendriks, Sarah; Grolleau, Jean-Louis; Khechimi, Myriam; Herlin, Christian; Chaput, Benoit
Abstract : Background: Venous congestion is a frequent problem in flap surgery. Other than surgical revision, there are a multitude of procedures in the literature to tackle this problem, but their effectiveness is not clear. Through a systematic review, we aimed to identify and evaluate the different interventions available for managing flap venous congestion. Methods: The MEDLINE, PubMed central, Embase, and Cochrane databases were searched. The study selection process was adapted from the PRISMA statement. All English and French original articles describing or comparing a method for managing flap venous congestion were included. For each article, a level of evidence was assigned, as defined by the Oxford Centre for Evidence-based Medicine. Lastly, we specifically analyzed the effectiveness of postoperative non-surgical methods. No formal analysis was performed. Results: Through literature searches carried out in various databases, we identified 224 articles. Finally, 72 articles were included. The majority of these studies had a low-level evidence. A total of 17 different methods (7 pre- and intraoperative, and 10 postoperative) were found. Concerning non-surgical methods, the most represented were leeches, local subcutaneous injection of heparin with scarification, venocutaneous catheterization, negative pressure therapy, and hyperbaric oxygen therapy. Conclusions: Risks of venous congestion of flaps must always be present in a surgeon's mind, at every stage of flap surgery. Apart from studies on the use of leeches, which have a significant follow-up and large enough patient numbers to support their efficacy, the low-level evidence associated with studies of other methods of venous congestion management does not allow us to draw a scientifically valid conclusion about their effectiveness.